Associations between self-reported mindfulness, driving anger and aggressive driving. (July 2018) - Stephens, A.N.; Koppel, S.; Young, K.L.; Chambers, R.; Hassed, C.
Highlights: Examined relationships between mindfulness, driving anger and aggressive driving. Mindfulness was negatively related to driving anger and aggressive driving. Results of SEM showed that mindfulness directly predicted driving anger but not driver aggression. Driving anger mediated the relationship between mindfulness and aggression. Mindfulness is likely to be an effective intervention for the reduction of anger and aggressive driving. Abstract: Anger and aggression on the roads is associated with how drivers evaluate the driving situation and the behaviour of other drivers. Consequently, both can be exacerbated when these evaluations are made superficially and/or when drivers have pre-existing negative schemas regarding certain types of road situations or users. Mindfulness is likely to have negative associations with anger and aggression because it promotes opposing appraisals. That is, it encourages emotion-regulation and involves acceptance of, but not reaction to, the current situation. To examine these associations, a total of 309 drivers responded to an online questionnaire assessing mindfulness, driving anger and aggressive driving. The results showed that mindfulness shared negative relationships with driving anger and self-reported aggressive driving. However, when these relationships were examined simultaneously using Structural Equation Modelling, mindfulness was found to relate only to anger and this, in turn, predicted aggressive driving. Further analysis showed that driving anger mediates the relationship between mindfulness and aggressive driving. These results suggest that mindfulness training may provide a promising intervention for drivers prone to driving anger and subsequent aggression.